The war against ourselves : nature, power and justice - Cock, Jacklyn (Wits University Press, 2007)
For many people 'nature' means wilderness and wild animals. It is experienced indirectly through magazines and television programmes or through visiting the highly managed environments of national parks. Nature, however, is not external, separate from the world of people - we live in nature and interact with it daily. In this book, Jacklyn Cock describes how these intricate and complex interconnections, seen and unseen, are often ignored. Each of the ten chapters examines an aspect of our relationship with nature: ignoring, understanding, enjoying, imitating, privatising, polluting, abusing, protecting as well as organising for nature. The concluding chapter deals with the growing inequality between the North and the South. The War Against Ourselves compels us to reexamine our relationship with nature, to change our practices and dissolve present binary divisions such as people vs. animals, economic growth vs. environmental protection, 'nature' vs. 'culture'. It demonstrates the need for an inclusive politics which brings together peace, social and environmental justice activists who believe that another world is both possible and necessary.